Court Workforce Racial Diversity and Racial Justice in Criminal Case Outcomes in the United States, 2000-2005 - Ward, Geoff ([Verlag nicht ermittelbar], 2009)
The purpose of this study was to determine whether workgroup racial composition is related to sentence outcomes generally, and racial differences in sentencing in particular, across federal districts. This collection contains information on federal court district characteristics. Data include information about the social context, court context, and diversity of the courtroom workgroup for 90 federal judicial districts provided by 50 judicial district context variables.